Color out of space [videorecording (DVD)] - Stanley, Richard, 1966-; Waller, Josh C., 1974-; Cage, Nicolas, 1965-; Richardson, Joely; Kilcher, Q'Orianka; Chong, Thomas, 1938-; Lovecraft, H. P. (Howard Phillips), 1890-1937 (RLJ Entertainment, 2020)
After a meteorite lands in the front yard of their farm, Nathan Gardner and his family find themselves battling a mutant extraterrestrial organism as it infects their minds and bodies, transforming their quiet rural life into a living nightmare.